New vaccine candidates as a scientific solution against the dream of tuberculosis vaccine. Issue 3 (July 2020) - Najafi, Azar; Mahdian, Nahid; Yousefi, Bahman; Karbalaei, Mohsen; kermanjani, Ali; Ezatpour, Behrouz; Eslami, Majid
Abstract : N/A: Tuberculosis (TB) is accounted for as one of the most important destructive infectious diseases for humans, which is caused by Mycobacterium tuberculosis . Studies have shown the severe effects of tuberculosis in patients, especially sensitive groups. Emergence and distribution of both multidrug-resistant (MDR) and extensively drug-resistant (XDR) strains have caused failure in the infection eradication. At present, BCG vaccine is the only most effective vaccine for the prevention of TB in childhood but its protection level in pulmonary TB in adult is very variable. Therefore, the need for an appropriate alternative vaccine instead of BCG is urgent. On the basis of the studies, cell-mediated immune (CMI) is known as the best immune response against TB infection. For this purpose, a desirable CMI response should be along with a balance between Th1, Th17, and T-reg cells. Several vaccine candidates have been evaluated in vitro and in vivo examinations, such as recombinant BCG (rBCG), DNA vaccines, and subunit vaccines. Factors, such as applicability of vaccine candidates in all individuals, cost-effectiveness, long-term immunity and stimulation of a wide range of responses are important factors. Now, most of these vaccines have entered in the phases of clinical trial (even IIB and III); however, these trials are complex, need a large number of individuals and need a long time. Funding for TB vaccine trials is an important issue, especially in poor countries. With preclinical safety precision studies, it is likely that at least one of these vaccines will develop into early clinical trials in the next few years.